THE MARKET OF SCIENTIFIC AND TECHNICAL PRODUCTS IN THE SYSTEM OF MARKET ECONOMY - M. Bapiyeva; A. Kocherbayeva (Scientific Journal of Pedagogy and Economics, 2019)
Theoretically investigated and defined features of the market of scientific and technical products. The analysis of factors influencing the development of the market of scientific and technical products is carried out; the specificity of scientific and technical products and its influence on the effectiveness of this market are shown. The specificity of subject-object relations of the market of scientific and technical products is investigated and it is determined that the process of forming this market should be considered from the perspective of creating an integral system of concepts, including objects, subjects, patterns and market interaction. The market of scientific and technical products is considered as part of a single market environment, along with the market of material resources, financial market, labor market, etc. All these markets are organically interconnected, the formation and functioning of each of them is carried out through interaction with others. The necessity of developing a common economic and technical policy for the development of the market of scientific and technical products and its infrastructure, the importance of coordinating the work of individual elements of the infrastructure of the market of scientific and technical products is substantiated.